Peran Literasi Tradisional dan Digital dalam Pembentukan Karakter Siswa di Era Pendidikan Abad 21 - Anita Candra Dewi (AIJER: Algazali International Journal Of Educational Research, 2024)
Abstract: This study discusses the role of digital literacy and traditional literacy in student character building in the 21st century education era. The rapid development of information technology requires students to not only be able to access information, but also to select and use information wisely. Digital literacy helps students face global challenges with critical and creative skills, while traditional literacy remains relevant in building moral and ethical values. The balance between these two types of literacy is crucial in shaping students with strong character, critical thinking and competitiveness in the midst of globalization. This article concludes that balanced and wise literacy can strengthen character education in preparing a generation ready to face the challenges of the 21st century.